1987
DOI: 10.1021/jo00392a036
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic destannylation: stereospecific introduction of electrophiles at the 21 position of (17.alpha.)-19-norpregna-1,3,5(10),20-tetraene-3,17.beta.-diols

Abstract: As part of our program to develop radiopharmaceuticals for the detection and diagnosis of estrogen-responsive breast cancer, we have focused on the use of organometallic substituents to facilitate the introduction of the radionuclide. As a result we initiated the application of organotin chemistry to the field of radiopharmaceutical chemistry in our preparation of the labeled antiestrogen [125I]iodotamoxifen.1-3 In that synthesis we could selectively lithiate and subsequently stannylate ortho to the (dimethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As part of our program to prepare novel high-affinity ligands for the estrogen receptor, we have undertaken the systematic development of novel probes for the hormone binding domain (HBD). In our previous studies we have reported the preparation of derivatives of estradiol bearing substituents at either the 11β-position (compounds 1a − f ) or the 17α-position (compounds 2a − d, 3a − d ) (Figure ). In each case, structure−activity relationships were developed which identified the effect of the substituent's properties on the ligand's affinity.…”
mentioning
confidence: 99%
“…As part of our program to prepare novel high-affinity ligands for the estrogen receptor, we have undertaken the systematic development of novel probes for the hormone binding domain (HBD). In our previous studies we have reported the preparation of derivatives of estradiol bearing substituents at either the 11β-position (compounds 1a − f ) or the 17α-position (compounds 2a − d, 3a − d ) (Figure ). In each case, structure−activity relationships were developed which identified the effect of the substituent's properties on the ligand's affinity.…”
mentioning
confidence: 99%
“…12 Hydrostannylation is a useful reaction for the preparation of carbon-functional organostannes and is the simplest and most direct route to transform alkynes into vinylstannes. 13 For the introduction of the iodine onto the vinyl substituent of the 17a-iodovinylestradiol we used the destannylation method. To obtain either the 20E or 20Z stannyl intermediates we previously4®-15 established a method using tri-n-butyltin hydride, with or without catalyst and with different reaction conditions (reaction time, temperature, and solvent polarity) to favor formation of either isomer.…”
Section: Resultsmentioning
confidence: 99%
“…4-Fluoro-7a-methyl-(17a^0S)-21-(tri-n-butylstannyl)vinylestradiol (10b). HPLC, ír = 16 min; MS m/z (relative intensity) 563 (M+ -C4H9,100), 562 (48), 561 (54), 558 (38), 507 (19), 505 (13), 429 (10), 329 (5), 310 (26), 290 (23), 245 (43).…”
Section: Methodsmentioning
confidence: 99%
“…Protection as a p -methoxybenzylidene acetal (Scheme ), followed by Wacker oxidation 66 led to methyl ketone (−)- 62 in modest yield. Conversion to the kinetic enol triflate 67 and treatment with in situ-generated Bu 2 CuLi·LiCN, furnished vinyl stannane (−)- 64 which was then transformed to vinyl iodide (−)- 60 (I 2 , CCl 4 ). , Although the overall yield for this five-step process was not suitable for large-scale material advancement, we proceeded with initial attempts to effect the coupling reaction.
18
…”
mentioning
confidence: 99%
“…Initially, we planned to generate vinyl lithium 66 from vinyl stannane (−)- 64 via transmetalation . However, when a mixture of (−)- 64 and n -butyllithium was stirred at −78 °C, no reaction occurred (Scheme ).…”
mentioning
confidence: 99%